Survival analysis of Bachelor of Secondary Education students of UM Digos College - Anter, Maria Cristine Joy; Gallos, Manelyn; Garzon, Dy Ann; Balacy, Garnette Mae (UM Digos Research Journal, 2016)
Survival analysis is a set of statistical methods used for examining data where the time until the occurrence of an event of interest is the outcome variable. This quantitative-descriptive correlational study aimed to investigate the survival of the Bachelor of Secondary Education students of UM Digos College for students’ batch from 2008 to 2012, 2009 to 2013, 2010 to 2014, 2011 to 2015, and 2012 to present. This study also determined the dropout rate and its relationship to the predictor variables, including the age, sex, and major that causes students to drop out. Kaplan-Meier Analysis and Log Rank Testing were used to analyze the enrolment data acquired from the Office of the Registrar of UM Digos College. Results revealed no significant difference on the dropping out of the students according to profile. Age, sex, and major are not factors that predict the probability of a student dropping out of school. Thus, it cannot be used to formulate a model that would indicate if a student has a greater chance of dropping out or not. It was also found out that students can drop out of school in between the second semester of their first year and the first semester of their second year in school.